The central issue in the rape trial - Mohamad Yunus, Mohamad Ismail (IIUM Press, 2015)
This book is not a study on why men rape women. The main focus of this book is to analyses and compares some of the legal issues and difficulties which rape presents in the criminal justice system in various jurisdictions and how it could and should be addressing them. The book begins with the historical conception of rape. It proceeds with the definition and scope of rape according to the modern views and perspectives. The main concern is on the law of consent. This is considered to be an important and crucial part in the law relating to sexual crimes and also right to be said as the heart of the rape trial. It begins with a discussion on the scope of consent and the difference between the concepts of “against her will” and “without her consent”. It then proceeds to elaborate the factors that vitiate consent, such as fraud or mistake, incapacity of the victims that covers consent given by minors and young persons, persons who lack of intellectual capacity and persons in the state of insensibility or unconsciousness. It continues with the vitiation of consent by threats or fear. This area will be divided into five chapters, first chapter deals with the standard and concept of consent, second chapter, third and fourth focus on the factors that vitiate consent such as threat or fear of bodily harm and threats or fear of non-bodily harm and other pressures such as sexual exploitation, economic pressure, unlawful detention or malicious prosecution and sexual blackmail. The last chapter discusses on the status of consent according to Islamic perspective.